Genotype and Allele Frequency of Methylenetetrahydrofolate Reductase 677CTmutation in Female Arabs residing in the United Arab Emirates - Khan, Gazala Afreen; Rahimi, Negin Mohammad Hossein; Gaeth, Mariam; Abdulhakim, Baraah; Nagy, Farah; Bassam, Reem (Journal of Medicine, 2024)
The MTHFR gene (Methylenetetrahydrofolate reductase), responsible for encoding the MTHFR enzyme, is vital for the body’s methylation processes, which are crucial for DNA synthesis, repair, and overall metabolic functions. Previous studies have shown that mutations in the MTHFR gene are associated with various diseases, including neural tube defects, male infertility, type II diabetes mellitus, cardiovascular diseases, and certain cancers. Additionally, abnormal methylation of the MTHFR gene can suppress other important genes such as methionine synthase, thymidylate synthase, choline kinase, and folate receptor genes. This suppression can result in a deficiency of the MTHFR enzyme, essential for proper cellular function, especially when a 677CT (C to T) transition occurs, leading to reduced enzyme activity. Despite the known implications of MTHFR gene mutations, no studies have probed these mutations in the female Arab population. To fill this gap, a pilot study was conducted to determine the prevalence of the MTHFR C677T gene mutation among 45 healthy Arab individuals in the United Arab Emirates. The study used the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method to detect the mutation. The study found that the mutated T allele had a 6% occurrence rate in the female Arab population. The genotype frequencies were 86.6% for the CC genotype, 13.3% for the CT genotype, and 0% for the TT genotype, indicating a relatively low prevalence of the MTHFR C677T polymorphism in Arab women. These findings provide preliminary data that can form the basis for further research on MTHFR gene mutations in this population, potentially enhancing the understanding and management of related health conditions. J MEDICINE 2024; 25: 141-148